Theoretical Analysis of the Performance of a Transparent Form of the Composition of Chemistry Education of Students in Higher Education - Qalandarov Farhod Astonaqulovich (Genius Publishing Group, 2022)
In this paper, the theoretical analysis of the performance of students in chemistry education in a transparent form is presented. In addition, the adoption of audiovisual information is based on the relationship between the external and internal activities of the teacher and the student, the audiovisual description of the teaching material presentation and their effectiveness theoretically.
Keywords: Chemistry; transparent; audiovisual information; programmed education